Theoretical study on the mechanism of the reaction for alkene hydroaminations catalyzed by chiral aldehyde. Issue 22 (4th June 2013) - Zhao, Jinfeng; Sun, Chuanzhi; Sun, Nan; Meng, Lin; Chen, Dezhan
<x xml:space="preserve">Abstract</x> Alkene hydroamination catalyzed by chiral aldehyde relying only on temporary intramolecularity is a new concept reaction. In this article, the reaction mechanism was investigated using density functional theory. The calculation results show that: (1) The reaction can be divided into two parts. The first part is a dehydration process involving a hemiaminal formation. The nitrone catalyst forms through rapid intermolecular nucleophilic addition of benzylhydroxylamine to chiral aldehyde precatalyst. The second part is a catalytic cycle, which involves an aminal formation—hydroamination—ring opening—product release process. (2) There are four enantioselective pathways related to the products of S and R configurations. Enantioselectivity is attributed to the different forming ways of a planar five‐membered ring. The preferred pathways for the S‐configuration product (S3) and R‐configuration product (R3) are confirmed. © 2013 Wiley Periodicals, Inc.